2008
DOI: 10.1055/s-2008-1038532
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Treatment of Duodenal Obstruction: Report on First Experiences in Latin America

Abstract: We conclude that a laparoscopic approach for duodenal obstruction can be performed safely and effectively and achieves a short hospital stay. Laparoscopic lysis of Ladd's bands is easy to perform, but duodenoduodenostomy requires advanced laparoscopic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12]. All studies were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were initially identified [3–12, 15, 16] from 2002 to 2014, of which four were case reports [3, 4, 15, 16] and were excluded. Eight studies were included [5–12], of which five focused on LRDA ( n = 67 patients) [5–9], and three were comparative between LRDA ( n = 57 patients) and conventional open repair ( n = 94 patients) [10–12]. All studies were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…However, these could be possibly outweighed by the technically challenging and time‐demanding nature of the LRDA, as well as by potential serious complications of laparoscopy such as paradoxical air embolism, cardiac arrest and cerebral stroke. Another important argument raised in favor of the LRDA is the less inhibition of bowel function it involves, and, thus, the less time to establish feeds and finally discharge [9]. This benefit, however, was not statistically confirmed in two of the three comparative studies between LRDA and open repair [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Case series of laparoscopic duodenoduodenostomy have demonstrated that the procedure is safe and efficacious. [3][4][5][6] Single-center descriptions of shortterm outcomes for both open and laparoscopic approaches have only recently been reported. 3,4,7,8 In these single-center series, conversion rates are highly variable (0%-26%), and reported complications are rare.…”
Section: Introductionmentioning
confidence: 99%